Parametric Study of Differential Absorption Lidar Systemfor Monitoring Toxic Agents in the Atmosphere - Veerabuthiran, S.; Dudeja, Jai Paul (Defence Science Journal, 2007)
Differential absorption lidar (DIAL) techniques are advantageously used these days fordetecting and monitoring traces of toxic agents located at several kilometer in the atmosphere.A theoretical study has been carried out to simulate the performance of a multiwavelength DIALsystem. Clouds of hydrazine, unsymmetrical dimethylhydrazine (UDMH), andmonomethylhydrazine (MMH), located at various ranges up to 5 km in the atmosphere, havebeen taken as examples of the toxic agents. It has been shown that a given lidar system cannotdetect any of these agents with a specific cloud thickness if the concentration of that agent isbelow a certain value (Nmin). It has also been shown that if the concentration level of a givenagent is above a certain value (Nmax) at a particular distance, this value cannot be quantified fora given lidar system although the identity as well as the location of that agent can still bedetermined. Further, for some typical parametric conditions, the required energy levels of thelaser to detect specific concentrations of these agents at different distances have been computed.Power levels of the return signals and the SNR values from different ranges have also beencalculated for each of these toxic agents for a given value of the laser transmitter energy.